Selective dopant segregation modulates mesoscale reaction kinetics in layered transition metal oxide. (June 2021) - Qian, Guannan; Huang, Hai; Hou, Fuchen; Wang, Weina; Wang, Yong; Lin, Junhao; Lee, Sang-Jun; Yan, Hanfei; Chu, Yong S.; Pianetta, Piero; Huang, Xiaojing; Ma, Zi-Feng; et al.
Abstract: Incorporation of foreign elements into the cathode material is broadly adopted by both academia and industry to improve the battery performance. The lack of an in-depth understanding for the underlying mechanism, however, makes it a largely try-and-error process with unsatisfactory efficiency and effectiveness. This is particularly true for the electrochemical reaction kinetics that is heterogeneous over a broad range of length scales and is determined collectively by the cathode's electronic structure, lattice configuration, and micro-morphology. Here we unveiled a facet-dependent dopant segregation effect in Zr-modified single-crystal LiNi0.6 Co0.2 Mn0.2 O2 cathode. By forming kinetically favored corners on the cathode particles, the presence of a trace amount of Zr critically modulates the mesoscale reaction kinetics. Our findings suggest that a delicately controlled dopant distribution is a viable strategy for designing the next-generation battery cathode with superior structural and chemical robustness. Graphical Abstract: ga1 Highlights: The impact of Zr modification on single crystalline NMC material was investigated from electrochemical kinetics perspective. The facet dependent Zr distribution on the NMC particle can modulate the Li-ion diffusion pathways. The electrochemical kinetically favored corners on the mesoscale were uncovered with advanced synchrotron imaging techniques.